Cesarean section and body mass index in children: is there a causal effect? - Lilian Fernanda Pereira Cavalcante; Carolina Abreu de Carvalho; Luana Lopes Padilha; Poliana Cristina de Almeida Fonseca Viola; Antônio Augusto Moura da Silva; Vanda Maria Ferreira Simões (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
Obesity is considered a global public health problem. Cesarean section has been associated with high body mass index (BMI) and increased obesity throughout life. However, this association has been challenged by some studies. This study aims to assess the causal effect of cesarean section on the BMI of children aged 1-3 years. This is a cohort study of 2,181 children aged 1-3 years, born in 2010, obtained from the BRISA Birth Cohort, in São Luís, state of Maranhão, Brazil. Sociodemographic variables, maternal characteristics, type of childbirth, morbidity, anthropometric measurements, and BMI were assessed. Marginal structural models with a counterfactual approach were used to check the causal effect of the type of childbirth on obesity, weighted by the inverse probability of selection and exposure. Out of the 2,181 children assessed (52% female), 50.6% were born by cesarean section, 5.9% of the newborn infants were large for gestational age, and 10.7% of them had excess weight. No causal effect of cesarean section on BMI was observed (coefficient = -0.004; 95%CI: -0.136; 0.127; p = 0.948). Cesarean section did not have a causal effect on the BMI of children aged 1-3 years.